Octreotide Treatment of Massive Hemorrhage due to Cytomegalovirus Colitis - Christopher N Andrews; Paul L Beck (Canadian Journal of Gastroenterology)
Cytomegalovirus (CMV)-associated colitis can result in abdominal pain, diarrhea, significant blood loss and perforation. The standard therapy for CMV colitis includes supportive measures and antiviral medications. Severe hemorrhage due to CMV colitis often necessitates surgical resection. We present a case of a patient who was undergoing chemotherapy for acute B-cell lymphoblastic leukemia and developed significant abdominal pain and diarrhea followed by massive hematochezia. Colonoscopy showed numerous actively bleeding deep ulcers in the cecum. A provisional diagnosis of CMV colitis was made and she was started on ganciclovir. Histological assessment confirmed the diagnosis of CMV colitis. She continued to bleed profusely per rectum over the following five days, passing up to 1 L to 1.5 L of blood per day. She required 10 units of packed red blood cells over this time period. The patient refused surgical intervention and after discussion of possible options, octreotide was instituted. Her blood loss stopped almost immediately and she required no further transfusions. She tolerated the medication well and was discharged home at a later date in stable condition. This is the first reported case of the use of octreotide in the treatment of massive hematochezia from CMV colitis.